Dietary Potassium Downregulates Angiotensin-I Converting Enzyme, Renin, and Angiotensin Converting Enzyme 2 - Vio, Carlos P.; Gallardo, Pedro; Cespedes, Carlos; Salas, Daniela; Diaz-Elizondo, Jessica; Mendez, Natalia (Frontiers in Pharmacology, 2020)
Background The importance of dietary potassium in health and disease has been underestimated compared with that placed on dietary sodium. Larger effort has been made on reduction of sodium intake and less on the adequate dietary potassium intake, although natural food contains much more potassium than sodium. The benefits of a potassium-rich diet are known, however, the mechanism by which it exerts its preventive action, remains to be elucidated. With the hypothesis that dietary potassium reduces renal vasoconstrictor components of the renin-angiotensin system in the long-term, we studied the effect of high potassium diet on angiotensin-I converting enzyme, renin, and angiotensin converting enzyme 2. Methods Sprague Dawley male rats on a normal sodium diet received normal potassium (0.9%, NK) or high potassium diet (3%, HK) for 4 weeks. Urine was collected in metabolic cages for electrolytes and urinary volume measurement. Renal tissue was used to analyze angiotensin-I converting enzyme, renin, and angiotensin converting enzyme 2 expression. Protein abundance analysis was done by Western blot; gene expression by mRNA levels by RT-qPCR. Renal distribution of angiotensin-I converting enzyme and renin was done by immunohistochemistry and morphometric analysis in coded samples. Results High potassium diet (4 weeks) reduced the levels of renin, angiotensin-I converting enzyme, and angiotensin converting enzyme 2. Angiotensin-I converting enzyme was located in the brush border of proximal tubules and with HK diet decreased the immunostaining intensity (P < 0.05), decreased the mRNA (P < 0.01) and the protein levels (P < 0.01). Renin localization was restricted to granular cells of the afferent arteriole and HK diet decreased the number of renin positive cells (P < 0.01) and renin mRNA levels (P < 0.01). High potassium intake decreased angiotensin converting enzyme 2 gene expression and protein levels (P < 0.01). No morphological abnormalities were observed in renal tissue during high potassium diet. The reduced expression of angiotensin-I converting enzyme, renin, and angiotensin converting enzyme 2 during potassium supplementation suggest that high dietary potassium intake could modulate these vasoactive enzymes and this effects can contribute to the preventive and antihypertensive effect of potassium.